Pediatric glioma stem cells: biologic strategies for oncolytic HSV virotherapy - Friedman, Gregory K.; Raborn, Joel; Kelly, Virginia M.; Cassady, Kevin A.; Markert, James M.; Gillespie, George Y. (Frontiers in Oncology, 2013)
While glioblastoma multiforme (GBM) is the most common adult malignant brain tumor, GBMs in childhood represent less than 10% of pediatric malignant brain tumors and are phenotypically and molecularly distinct from adult GBMs. Similar to adult patients, outcomes for children with high-grade gliomas (HGGs) remain poor. Furthermore, the significant morbidity and mortality yielded by pediatric GBM is compounded by neurotoxicity for the developing brain caused by current therapies. Poor outcomes have been attributed to a subpopulation of chemotherapy and radiotherapy resistant cells, termed ‘glioma stem cells’ (GSCs), ‘glioma progenitor cells’, or ‘glioma-initiating cells', which have the ability to initiate and maintain the tumor and to repopulate the recurring tumor after conventional therapy. Future innovative therapies for pediatric HGGs must be able to eradicate these therapy-resistant GSCs. Oncolytic herpes simplex viruses, genetically engineered to be safe for normal cells and to express diverse foreign anti-tumor therapeutic genes, have been demonstrated in preclinical studies to infect and kill GSCs and tumor cells equally while sparing normal brain cells. In this review, we discuss the unique aspects of pediatric GSCs, including markers to identify them, the microenvironment they reside in, signaling pathways that regulate them, mechanisms of cellular resistance, and approaches to target GSCs, with a focus on the promising therapeutic, genetically engineered oncolytic herpes simplex virus (HSV).